Preventing Health Care Provision Errors: Medical Ethics and Clinical Documentation - Edwards, Geneva M. (New Advances in Medicine and Medical Science Vol. 2, 2023)
The concept of the standard of care is often discussed among healthcare providers, and yet, not understood by many. Healthcare providers are held to a higher standard than the general members of the public. This higher standard affects both their clinical and personal lifestyle when they are not at work. The field of legal medicine covers a wide range of topics related to law, medicine, ethics, human rights, and individual rights. This area of expertise is required in the healthcare industry because it is the responsibility of healthcare professionals to always act in the best interests of their patients. If healthcare professions fail to meet this duty they can and will be charged in a court of law. Medical malpractice is defined as the legal cause of action that arises when a healthcare professional fails to uphold the standard of care in their field, harming a patient in the process. This can happen when a patient suffers harm as a result of a healthcare professional's negligence. Negligence is a common medical malpractice claim, involving inappropriate, unqualified, or sub-standard care provision of a patient by a physician, dentist, nurse, pharmacist, or other healthcare professional. When a healthcare provider does not meet the standard of care, they have breached their contract with their patient. Carelessness is a by-product produced of providers who do not take the time or have enough time to perform their necessary duties in healthcare provision. There are a few sure ways providers can be successful in avoiding mishaps of healthcare provision. The best research and clinical expertise must be reviewed by a large number of healthcare professionals in order to help them meet patients' needs beyond the scope of optimal care delivery and help them avoid any mishaps along the way. This chapter has only touched the surface in preventing mishaps in healthcare provision. More research in depth is required to help us understand how to deal with inadequacies when caring for patients.